Anexo documental: - Documental, Anexo (Revista Nuevos Paradigmas de las Ciencias Sociales Latinoamericanas, 2020)
Brief amici curiae of the American Psychological Association, California Psychological Association, American Psychiatric Association, National Association of Social Workers, and National Association of Social Workers, California Chapter in support of the parties challenging the marriage exclusion